Magnetic hardening and domain structure in Co/Pt antidots with perpendicular anisotropy. (12th January 2017) - Bran, C; Gawronski, P; Lucas, I; del Real, R P; Strichovanec, P; Asenjo, A; Vazquez, M; Chubykalo-Fesenko, O
Abstract: (Co(0.4 nm)/Pt(0.7 nm)) x ( x   =  10, 20, 30) multilayer antidot thin films (films with arrays of nanoholes) have been grown by dc sputtering onto self-assembled pores of anodic alumina membranes with a tailored diameter and a fixed inter-hole distance. The magnetic behavior has been quantified by vibrating sample magnetometry, and the surface magnetization patterns have been imaged by magnetic force microscopy. The magnetization reversal mechanism is characterized by two steps depending on the film thickness and antidot diameter. These steps are ascribed to the nucleation and demagnetization of magnetic stripe domains. Their presence confirms the perpendicular anisotropy of the multilayer antidot films. The coercivity of antidot thin film is larger than that of the continuous films due to additional pinning centers provided by antidots. The width of the stripe domains increases as a function of film thickness. The demagnetization is further investigated through micromagnetic simulations that are in agreement with the measured hysteresis loops and their features. Different reversal mechanisms and an increase of the domain width in antidot thin films are also confirmed as a function of the magnetic anisotropy, antidot diameter and thickness of the thin film. The presence of antidots with a designed geometry is revealed to be successful in tailoring the coercivity of the thin films and magnetic patterns, which is relevant for advances in nanoscale technologies.